Liver resection rate following downsizing chemotherapy with cetuximab in metastatic colorectal cancer: UK retrospective observational study. Issue 4 (April 2015) - Malik, H.; Khan, A.Z.; Berry, D.P.; Cameron, I.C.; Pope, I.; Sherlock, D.; Helmy, S.; Byrne, B.; Thompson, M.; Pulfer, A.; Davidson, B.
Abstract Aims The high objective response rate to cetuximab along with chemotherapy in patients with colorectal liver metastases makes it an effective downsizing protocol to facilitate surgery in those with initially unresectable disease. Adoption of this strategy has been variable in the UK. A retrospective observational study was conducted in 7 UK specialist liver surgical centres to describe the liver resection rate following a downsizing protocol of cetuximab and chemotherapy and to evaluate the quality and efficiency of processes by which the treatment was provided. Methods Data were collected in 2012 by reviewing medical records of patients with colorectal metastases confined to the liver, defined as unresectable without downsizing therapy at first review by a specialist Multi Disciplinary Team (MDT). Results Sixty patients were included; 29 (48%) underwent liver resection following cetuximab and chemotherapy. Of the 29, 17 (59% or 28% of all patients) achieved R0 resection and 7 (24% or 12% of all patients) R1 resection. All treated patients were KRAS wild-type. Conclusion In specialist liver surgical centres, where patients are evaluated for liver resection, optimal management by MDT using KRAS testing, cetuximab and chemotherapy results in a 28% R0 resection rate in patients with initially unresectable colorectal cancer liver metastases.